MORPHOLOGICAL CHARACTERISTIC DIFFERENCE BETWEEN MOSQUITOES VECTOR FOR MALARIA AND DENGUE FEVER - Syubbanul - Wathon; Kartika Senjarini; Rike Oktarianti; Ratis Nour Sholichah; Ahmad Tosin (BIOEDUKASI, 2020)
Malaria and Dengue Haemorrhagic Fever (DHF) are two major tropical diseases in East Java. The pathogens of these diseases are transmitted to human hosts via haematophagy by vector mosquitoes. Anopheles spp. specifically transmits Plasmodium parasites which cause Malaria, while Aedes spp. transmits Dengue viruses that cause DHF. Bangsring, Banyuwangi is one of the endemic areas of Malaria, while Jember is one of endemic areas of DHF. Two species of Malaria vectors i.e Anopheles vagus and Anopheles sundaicus have been found from several samplings which were conducted in Bangsring region. This mosquitoes have been previously identified as a major vector for malaria. Aedes aegypti and Aedes albopictus, which were major vectors for DHF, have been easily found in Jember during our sampling for any season of the year. This research wanted to differentiate the morphological characteristic of those vectors for malaria and Dengue. Adult mosquitoes can be distinguished from one another by characterizing their morphological features. Palpi, wings, and legs characteristics are commonly used as determination keys in Anopheles sp., while thoraxes and legs characteristics are used as identification keys in Aedes sp. Morphological identification is considered as the basic necessity in understanding and determining bionomic of mosquito vector. This is very important in developing effective and efficient mosquito vector control strategies, which is also an important step to prevent the death risks associated with Malaria and DHF cases.